2009
DOI: 10.1007/s11128-009-0137-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-Markovian entanglement dynamics of two qubits interacting with a common electromagnetic field

Abstract: We study the non-equilibrium dynamics of a pair of qubits made of two-level atoms separated in space with distance r and interacting with one common electromagnetic field but not directly with each other. Our calculation makes a weak coupling assumption but no Born or Markov approximation. We write the evolution equations of the reduced density matrix of the two-qubit system after integrating out the electromagnetic field modes. We study two classes of states in detail: Class A is a one parameter family of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 49 publications
(148 reference statements)
3
39
0
Order By: Relevance
“…[38] for two qubits in a common electromagnetic field). This is what one might anticipate would happen for our model in the more general cases.…”
Section: Dynamics Of Entanglement: An Examplementioning
confidence: 99%
See 1 more Smart Citation
“…[38] for two qubits in a common electromagnetic field). This is what one might anticipate would happen for our model in the more general cases.…”
Section: Dynamics Of Entanglement: An Examplementioning
confidence: 99%
“…Doing a level reduction scheme for both oscillators and viewing the harmonic oscillator bath as a field would reduce our 2HO QBM model to that of two qubits interacting either directly or indirectly through a common field. An example of the latter situation is studied in [38]. One can use the exact master equations here under appropriate simplifications to describe the nonMarkovian dynamics of such systems.…”
Section: B Decoherence and Disentanglementmentioning
confidence: 99%
“…For example, qubits have great advantages in certain computational tasks compared to classical bits because of quantum coherence and quantum entanglement. However, for an open quantum system, mutual effects due to the coupling between the system and environment are inevitable and result in very complex reduced dynamics including dissipation, fluctuation, decoherence and disentanglement [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In particular those explicitly taking into account the distance between the particles are of relevance [39][40][41]. In these works it was shown that for certain initial states, the distance between the qubits can qualitatively change the entanglement dynamics.…”
Section: Introductionmentioning
confidence: 99%